2020
DOI: 10.21037/atm.2020.02.164
|View full text |Cite
|
Sign up to set email alerts
|

Induced pluripotent stem cells for the treatment of liver diseases: challenges and perspectives from a clinical viewpoint

Abstract: The only curative treatment for severe end-stage liver disease (ESLD) is liver transplantation (LT) but it is limited by the shortage of organ donors. The increase of the incidence of liver disease has led to develop new therapeutic approaches such as liver cell transplantation. Current challenges that limit a wider application of this therapy include a limited cell source and the poor engraftment in the host liver of cryopreserved hepatocytes after thawing. Induced pluripotent stem cells (iPSCs) that can be d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 98 publications
1
3
0
Order By: Relevance
“…Many attempts have been reported to produce hepatocytes on a large scale using human pluripotent stem cells [12,70]. However, one limitation of conventional differentiation in 2D configuration is its low differentiation efficiency [18,27]. According to our results, the expression of hepatoblast marker AFP was significantly increased at both the mRNA and protein levels in 2D-derived HLC, which indicated that 2Dderived HLC resembled hepatoblast cells rather than mature hepatocytes (supplementary figures 1(C) and (D)).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Many attempts have been reported to produce hepatocytes on a large scale using human pluripotent stem cells [12,70]. However, one limitation of conventional differentiation in 2D configuration is its low differentiation efficiency [18,27]. According to our results, the expression of hepatoblast marker AFP was significantly increased at both the mRNA and protein levels in 2D-derived HLC, which indicated that 2Dderived HLC resembled hepatoblast cells rather than mature hepatocytes (supplementary figures 1(C) and (D)).…”
Section: Discussionsupporting
confidence: 51%
“…The highly proliferative pluripotent stem cells can yield clinically-relevant amount of HLC for the construction of 3D liver tissue [17]. However, HLC generated from pluripotent stem cells often show an immature phenotype comprising features such as a high expression of alpha-fetoprotein (AFP) and diminished level of metabolic activity, and therefore resemble fetal rather than adult hepatocytes [18,19]. Hence, enhancing the maturity of HLC derived from pluripotent stem cells represents an important goal for liver tissue engineering.…”
Section: Introductionmentioning
confidence: 99%
“…Many protocols have been developed for differentiating SCs into HLCs with different approaches, such as mimicking liver development through the sequential addition of growth factors and cytokines ( Cai et al, 2007 ; Hay et al, 2008b ; Brolén et al, 2010 ), modulation of signaling pathways ( Hay et al, 2008a ) or by using epigenetic modifiers ( Sharma et al, 2006 ; Dong et al, 2009 ; Norrman et al, 2013 ). Currently, most work has been developed using induced pluripotent SCs (iPSCs) isolated from adult tissues in an non-invasive way, with promising outcomes ( Sauer et al, 2014 ; Sirenko et al, 2016 ; Yamashita et al, 2018 ; Pareja et al, 2020 ). An example is the work from Gao and Liu (2017) , that revealed that iPSC-derived HLCs resembled hpHep more closely than most hepatoma cell lines in global gene expression profiles, specifically in the expression of genes involved in hepatotoxicity, drug-metabolizing enzymes, transporters, and nuclear receptors.…”
Section: Liver In Vitro Models For Toxicological Smentioning
confidence: 99%
“…These cells could mediate the reconstruction of hypoimmunogenic liver sinusoids in vitro paving the way for regenerative medicine in liver diseases. Chronic liver diseases, characterized by a massive loss of hepatocyte function, and several inborn metabolic diseases require liver transplantation that is limited by the shortage of organs [19,20]. Currently, primary cryopreserved hepatocytes are the gold standard for liver cell therapy [21], although they are characterized by low cell renewal, loss of their phenotypic characteristics and functions once isolated, and poor engraftment in the host liver.…”
Section: Discussionmentioning
confidence: 99%